2014
DOI: 10.1002/dmrr.2573
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus: influences on cancer risk

Abstract: Diabetes mellitus and cancer are common conditions, and their co-diagnosis in the same individual is not infrequent. The relative risks associated with type 2 diabetes are greater than twofold for hepatic, pancreatic, and endometrial cancers. The relative risk is somewhat lower, at 1.2-1.5-fold for colorectal, breast, and bladder cancers. In comparison, the relative risk of lung cancer is less than 1. The evidence for other malignancies (e.g. kidney, non-Hodgkin lymphoma) is inconclusive, whereas prostatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 137 publications
(186 reference statements)
1
67
0
Order By: Relevance
“…Unopposed estrogen has been shown to increase the risk of EC development, as estrogens stimulate endometrial cell proliferation and inhibit apoptosis (3). Additionally, diseases associated with insulin resistance, such as obesity, type II diabetes mellitus and polycystic ovary syndrome (PCOS), are considered significant risk factors for the development and progression of type I EC (4)(5)(6). Insulin resistance is a condition in which target tissues have decreased sensitivity to insulin, and blood insulin levels consequently increase to maintain normal glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Unopposed estrogen has been shown to increase the risk of EC development, as estrogens stimulate endometrial cell proliferation and inhibit apoptosis (3). Additionally, diseases associated with insulin resistance, such as obesity, type II diabetes mellitus and polycystic ovary syndrome (PCOS), are considered significant risk factors for the development and progression of type I EC (4)(5)(6). Insulin resistance is a condition in which target tissues have decreased sensitivity to insulin, and blood insulin levels consequently increase to maintain normal glucose levels.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, although there are limited studies, Zendehdel et al (11) reported that T1DM can increase the incidence risk ≤20% for gastric, endometrial and cervical cancer in the general Swedish population. T1DM appeared to be correlated with a moderate excess cancer risk overall, and risks of specific types of cancer that differ from those associated with T2DM (12). To the best of our knowledge, the exact values of estimated risk, however, may vary due to study design, the impact of confounding factors and ethnic differences, including genetic susceptibility, life-style behaviors, specific environmental exposures and varying biological effects of diabetes across populations.…”
Section: Diabetes and Risk Ratio To Cancermentioning
confidence: 90%
“…According to several meta-analyses, an increased frequency of malignancies in diabetic patients has been attributed to various general and local mechanisms (1,3,4,10,12).…”
Section: Incidence Of Different Types Of Cancer Among Diabetic Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Current researches show that especially pancreatic, liver, endometrial, colorectal, bladder and breast cancer incidences are increased by the presence of diabetes. 3,4 Multiple and complex mechanisms were postulated for the association between diabetes and cancer. These associations could be causal or because of common risk factors since type 2 diabetes and cancer are common chronic disorders.…”
Section: Type 2 Diabetes Mellitus and Cancermentioning
confidence: 99%